2008
DOI: 10.1101/gad.471908
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide location analysis reveals a role of TFIIS in RNA polymerase III transcription

Abstract: TFIIS is a transcription elongation factor that stimulates transcript cleavage activity of arrested RNA polymerase II (Pol II). Recent studies revealed that TFIIS has also a role in Pol II transcription initiation. To improve our understanding of TFIIS function in vivo, we performed genome-wide location analysis of this factor. Under normal growth conditions, TFIIS was detected on Pol II-transcribed genes, and TFIIS occupancy was well correlated with that of Pol II, indicating that TFIIS recruitment is not res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 52 publications
3
65
0
Order By: Relevance
“…The spatial Rad2 distribution on the longest class III gene, SCR1, was similar to that of Pol III (Supplemental Fig. S2D; Ghavi-Helm et al 2008). We also confirmed the presence of Rad2 on telomeric regions (Supplemental Fig.…”
Section: Genome-wide Location Analysis Of Rad2supporting
confidence: 70%
“…The spatial Rad2 distribution on the longest class III gene, SCR1, was similar to that of Pol III (Supplemental Fig. S2D; Ghavi-Helm et al 2008). We also confirmed the presence of Rad2 on telomeric regions (Supplemental Fig.…”
Section: Genome-wide Location Analysis Of Rad2supporting
confidence: 70%
“…A conventional ChIP experiment on the rDNA locus (Fig. S2) confirmed that Sub1 (but not TFIIIC) bound all along the rDNA gene locus but preferentially to the Pol I-transcribed region, an enrichment profile similar to that of TFIIS, a protein involved in Pol II transcription that has been shown recently to play a role in Pol III transcription (19).…”
Section: Resultsmentioning
confidence: 87%
“…1C, Sub1 was detected significantly all along the SCR1 gene and over the tRNA Ileu gene, but not on the intergenic regions that separate these loci. A comparison of the enrichment profile of Sub1 across the SCR1 gene with that of TFIIIC, TFIIIB and Pol III (19) suggested a colocalization of Sub1 with Pol III.…”
Section: Resultsmentioning
confidence: 99%
“…RNAPIII, TFIIIB, and TFIIIIC show the expected profiles (Supplemental Fig. S5; Ghavi-Helm et al 2008). Nab2 has its highest occupancies at the 5 ′ end of SCR1 (Supplemental Fig.…”
Section: Nab2 Is Required For Stable Association Of Tfiiib With the Pmentioning
confidence: 91%